Urinary metabonomic study of the surface layer of Poria cocos as an effective treatment for chronic renal injury in rats - Zhao, Ying-Yong; Li, Hai-Tao; Feng, Ya-Long; Bai, Xu; Lin, Rui-Chao (Journal of ethnopharmacology, 2013)
Poria cocos Wolf (Polyporaceae) is a well-known medicinal fungus. The epidermis of the sclerotia (“Fu-Ling-Pi” in Chinese) is used as a diuretic and traditionally used for promoting urination and reduce edema. Traditional Chinese medicines (TCM) treat many diseases through multi-components, multi-ways and multi-targets. However, the molecular mechanisms of TCM are not yet well understood. In the present work, ultra performance liquid chromatography-based metabonomics analysis was applied to investigate the urinary metabolite profiling of the renoprotective effect of FLP on adenine-induced chronic kidney disease (CKD) rat model and involved possible mechanism. A metabonomic approach based on ultra performance liquid chromatography coupled with quadrupole time-of-flight high-sensitivity mass spectrometry and a novel mass spectrometryElevated Energy data collection technique was developed. The resulting dataset was analyzed by principal component analysis and partial least squares discriminant analysis. The identification of all potential biomarkers was performed using reference standard by comparing their mass spectra, MSE fragments information, isotopic pattern and MassLynx i-FIT algorithm. By partial least squares-discriminate analysis, 15 biomarkers in rat urine were identified and 11 of them were related to the pathway of adenine metabolism and amino acid metabolism. Among these biomarkers, eight biomarkers like adenine, l-acetylcarnitine, 8-hydroxyadenine, hypoxanthine, creatine, methionine, phytosphingosine and phenylalanine were reversed to the control level in FLP-treated group and six biomarkers like 2,8-dihydroxyadenine, indole-3-carboxylic acid, 3-methyldioxyindole, ethyl-N2-acetyl-l-argininate, 3-O-methyldopa and xanthurenic acid were reversed to high control group by FLP, which indicates that the urinary metabolic pattern significantly changed after FLP treatment. Our study indicates that FLP treatment can ameliorate CKD by intervening in some dominating metabolic pathways, such as adenine metabolism and amino acid metabolism. The metabonomic results not only supplied a systematic view of the development and progression of CKD and mechanism studies of FLP but also provided the theoretical basis for the prevention or treatment of CKD. [Display omitted]